O processo de formação inicial de professores no município de Alegre-ES: A compreensão dos discentes sobre a educação especial - Lordeiro, Mariana Aparecida (2021)
The objective of this work was analyse different degree students’ understanding about Special Education in graduation courses at Universities, in the city of Alegre-ES. Theoretical basis to discuss about teachers training is based on Gatti, Saviani, Scheibe and Netto; articulated the contributions of Jannuzzi, Garcia and Michels, to think over Special Education, on the Inclusive Education perspective, in the initial teachers’ training. In this way, this paper carried out a qualitative research as a case study type. The instruments used to produce information were questionnaires that were applied on final degree students from three Universities in the city of Alegre-ES; and the document consultation was made on the curriculum matrices of these graduation courses. The content analysis was used to analyse the data. Based on the analysis, it was possible to observe that the Special Education is on the curriculum of all three Universities, as a priority on the compulsory subjects of the Special Education field. However, the degree students point out the need for this topic to be more covered and deepened discuss during the course, in other subjects of the curriculum matrices or in the specific subjects of Special Education. Regarding to the students’ comprehension about Special Education, it can be pointed its articulation with the school inclusion process, respect for differences and accessibility. The students highlight the importance of theoretical-pratical knowledge faced to the schooling process of the target audience of Special Education in the initial training process. In reference to the way this theme is covered during the degree courses, most degree students consider it adequate, however, they point out the absence of specific training and little experience of teachers in the field. Furthermore, they highlight that the didactic is adequate using different methodological strategies. In the meantime, different methods are proposed based on case studies, problem-situations and practices that promote contact with the target audience in Especial Education in schools. In this way, this study points the importance and need to (re) think the place of Special Education on the initial training of teachers in order to provide the construction of knowledges that enable the development of inclusive educational practices from the future teachers to all students.